C.B. Strike : the series [videorecording (DVD)] - Richards, Ben, 1964-; Edge, Tom; Burke, Tom, 1981-; Grainger, Holliday, 1988-; Shaw, Martin, 1945-; Logan, Kerr; Galbraith, Robert (Warner Home Video, 2018)
Cormoran Strike is a war veteran turned private detective operating out of a tiny office in London's Denmark Street. Though he's wounded both physically and psychologically, Strike's unique insight and his background as an SIB Investigator prove crucial in solving complex cases that elude the police.